Assessing Lean Thinking in Hospital: A Conceptual Framework - O, Yancy; Ayuningtyas D (Community Medicine and Education Journal, 2024)
Currently, the lean thinking system has not been implemented in all hospitals in Indonesia, where there is a lot of waste that affects the low quality of service and patient safety. The aims of this study is to develop a conceptual framework as a basis for quantitative assessment of lean thinking systems in Indonesian Hospitals to improve services, increase patient satisfaction and improve hospital quality. In preparing the conceptual framework for the quantitative assessment model of the lean thinking system index, a literature study was carried out through a literature search for journals from several countries and textbooks using the keywords "lean thinking" and "hospital". Literature review was conducted through several data sources, including ProQuest, Taylor & Francis, SpringerLink, and ScienceDirect. The types of literature were research articles with range of years 2012–2022. In total, 86 articles were obtained. The next stage includes screening, checking for duplication of articles and filtering articles based on inclusion criteria, so that there are 8 articles remaining. The 8 articles were reviewed to create a new conceptual framework. The result of the study is lean thinking model designed based on current conditions, expected future conditions, implements lean thinking, and maintains it with continuous improvement. This model is still in the early stages of research and forms the basis for the preparation of subsequent instruments. Currently the model is used in the hospital where the author works. The proposed conceptual framework can become the necessary basis for index development, which can then be used as a basis for further policy interventions to improve services in hospitals. In the end, this model can also improve quality and patient satisfaction.